Effect of combination of D-glycin and antibiotics on biofilm formation by clinical, food and environmental isolates of Escherichia coli - Marwa H. Mtashar Al-Khafaji; Heba .K. Tawfeeq; Beadaa A. Mahdii (World Journal of Experimental Biosciences, 2016)
The ability of many bacteria to adhere to surfaces and form biofilm makes the treatment of infections so difficult and has major consequences in a variety of industries such as food industry. Biofilm generates a persistent cause of contamination, thus, in the present study; inhibition of biofilm formation efficacy of the combination of D-glycin with antibiotics was compared with the antibiotic alone against Escherichia coli biofilm formation. It was found that the synergetic action of antibiotics with D-glycin was effective on inhibition of biofilm formation. The isolates ability to form biofilm was assayed using the tissue culture plate and Congo-red agar methods and findings of this study were source related; since food origin isolates were more biofilm producers when the Congo-red agar was used as compared with tissue culture plate method. Minimum inhibitory concentration (MIC) of D-glycin, imipenem and ceftriaxone were determined. The combinations of D-glycin with antibiotics inhibited bacterial biofilm formation more than the antibiotics imipenem and ceftriaxone separately. Susceptibility test to eight antibiotics: Imipenem, ceftriaxone, ampicillin, amoxicillin, cephalexin, clarithromycin, gentamycin and tetracycline; was performed on planktonic cells, and the cells exhibited different sensitivity patterns to them depending on their source.
Keywords: Biofilm, Ceftriaxone, D-glycin, Escherichia coli, Imipenem.